MUTU FISIK BERAS GENOTIP LOKAL PADI SAWAH YANG DITANAM DI SENTRA PRODUKSI SUMATERA BARAT - Lastri Nur, Azwir Anhar Anizam Zein (SEMIRATA 2015, 2015)
The physical quality of rice is not only determined by its genotype inserted but also affected by environmental factors. This research was conducted in four locations in West Sumatera i.e Solok, Bukittinggi, Pariaman and Pesisir Selatan. The local rice genotypes used were Ciredek, Anak Daro, Randah Putiah, Cantiak Manih, Mundam, Bakwan and Sarai Sarumpun. The randomized block design was used in each location. Observations was focused on grain physical quality which was grouped into 5 categories, i.e head grain, broken grain, chalky grain, brewers grain and damage grain. Observation on rice quality was done in Plant Physiology Laboratory of Biology department at Padang State University. The data obtained was analyzed by inserted ANOVA and continued with DNMRT test at 5% error level.The results showed that interaction genotype and location affect the physical quality. There was interaction gxe on head and broken rice. Â Chlaky grain was affected only by genotype inserted. In conclusion some quality of rice are determined by interaction genotype and environment. The others were affected by genotype Keywords: quality, local rice, genotype, west sumatera